PENGARUH KARAKTERISTIK PERUSAHAAN DAN KEPEMILIKAN INSTITUSIONAL PADA NILAI PERUSAHAAN DENGAN CSR SEBAGAI VARIABEL INTERVENING - Permana Putra, I Putu Deri; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 21 No 2 (2017)DO - 10.24843/EJA.2017.v21.i02.p15, 2017)
A company is established with the aim to achieve maximum corporate value. The value of the company is very important because it reflects the company's performance and stock prices that can affect investors' perceptions of the company. Companies as one economic entity generally have short-term and long-term goals. The short-term goal of a company is to maximize profits, while its long-term goal is to increase the company's value. Factors that can affect the firm's value are profitability, leverage, firm size, institutional ownership and corporate social responsibility. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange period 2013-2015. The number of samples of 63 companies obtained by purposive sampling technique. Data analysis technique used in this research is path analysis technique (path analysis). The result of testing in this research shows that profitability, leverage, company size, and institutional ownership have positive effect on firm value. While the corporate social responsibility variable does not affect the value of the company. Variable profitability and firm size, have a positive effect on corporate social responsibility. While leverage and institutional ownership variables have no effect on corporate social responsibility. Corporate social responsibility variables act to mediate the effect of firm size on firm value. But the absence of a corporate social responsibility role mediates the effect of profitability, leverage, and institutional ownership on corporate value.